An identification scheme based on bivariate function hard problem - Tea, Boon Chian; Kamel Ariffin, Muhammad Rezal (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
Recently, an identification scheme based on Diophantine Equation Hard Problem is proposed. The scheme was proven secure against impersonation under passive attack, assuming that solving Diophantine Equation Hard Problem is hard. However, further simulation showed that there exists non-negligible probability that the scheme can be easily impersonated without knowing the secret parameter. In this paper, another identification scheme based on Bivariate Function Hard Problem which is specific problem of Diophantine Equation Hard Problem (DEHP) is proposed. We prove by assuming that solving Bivariate Function Hard Problem is hard, our scheme is secure against the impersonation under passive, active and concurrent attacks. Also, our proposed is again more efficient than some selected schemes since the structure of our hard problem is similar to DEHP.